Bortezomib plus melphalan and prednisone for initial treatment of multiple myeloma - San Miguel, J.F.; Schlag, R.; Khuageva, N.K.; Dimopoulos, M.A.; Shpilberg, O.; Kropff, M.; Spicka, I.; Petrucci, M.T.; Palumbo, A.; Samoilova, O.S.; Dmoszynska, A.; Abdulkadyrov, K.M.; et al. (New England Journal of Medicine, 2008)
Background: The standard treatment for patients with multiple myeloma who are not candidates for high-dose therapy is melphalan and prednisone. This phase 3 study compared the use of melphalan and prednisone with or without bortezomib in previously untreated patients with multiple myeloma who were ineligible for high-dose therapy. Methods: We randomly assigned 682 patients to receive nine 6-week cycles of melphalan (at a dose of 9 mg per square meter of body-surface area) and prednisone (at a dose of 60 mg per square meter) on days 1 to 4, either alone or with bortezomib (at a dose of 1.3 mg per square meter) on days 1, 4, 8, 11, 22, 25, 29, and 32 during cycles 1 to 4 and on days 1, 8, 22, and 29 during cycles 5 to 9. The primary end point was the time to disease progression. Results: The time to progression among patients receiving bortezomib plus melphalan-prednisone (bortezomib group) was 24.0 months, as compared with 16.6 months among those receiving melphalan-prednisone alone (control group) (hazard ratio for the bortezomib group, 0.48; P<0.001). The proportions of patients with a partial response or better were 71% in the bortezomib group and 35% in the control group; complete-response rates were 30% and 4%, respectively (P<0.001). The median duration of the response was 19.9 months in the bortezomib group and 13.1 months in the control group. The hazard ratio for overall survival was 0.61 for the bortezomib group (P=0.008). Adverse events were consistent with established profiles of toxic events associated with bortezomib and melphalan-prednisone. Grade 3 events occurred in a higher proportion of patients in the bortezomib group than in the control group (53% vs. 44%, P=0.02), but there were no significant differences in grade 4 events (28% and 27%, respectively) or treatment-related deaths (1% and 2%). Conclusions: Bortezomib plus melphalan-prednisone was superior to melphalan-prednisone alone in patients with newly diagnosed myeloma who were ineligible for high-dose therapy. (ClinicalTrials.gov number, NCT00111319.). Copyright © 2008 Massachusetts Medical Society. All rights reserved.